PERSEPSI PENGUNJUNG TERHADAP FUNGSI RUANG TERBUKA HIJAU TUNJUK AJAR INTEGRITAS - Anggi Pratama; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in Green Open Space Tunjuk Ajar Integritas located in JL. Jend. Ahmad Yani Pekanbaru City. With Problem Formulation (1) How is the activity of the people who visit Green open spaces Space Tunjuk Ajar Integritas? (2) How does the Perception of Visitors to Green Open Space Appoint Space Tunjuk Ajar Integritas ?. with the aim of this study the first is the activity of the community who visited the green open space Intelligence of Integrity and to know how the perception of visitors to the function of green open space Space Tunjuk Ajar Integritas. This research is descriptive quantitative research by taking sample as respondent as many as 50 people in choosing with accidental sampling technique . for thecollect data in this research using obserbasi way, interview and documentation. Based on the result of the research, it can be concluded that (1) the activity done by the visitors in green open space Space Tunjuk Ajar Integritas of 50 respondents interviewed (44%) doing recreation activity, exercise activity (30%), doing economic activity (10%), conducting interacting activities (12%), as a stop room (4%). (2) a good public perception of the Green Open Space Space Tunjuk Ajar Integritas. The choice of the form of the area, which is large enough and can be utilized with various outdoor activities of the community, is a community choice that can be considered quite good. Form of green space like this can also support community activities Pekanbaru City. Keywords: Activity, Perception, Function, Open Space Green